Ecology and patch dynamics of Megaphrynium macrostachyum (Benth.) Milne-Redh. (Marantaceae) in the south-west Central African Republic - (:unkn) unknown (My University, 2003)
Herbs in the family Marantaceae are an important component of moist semi-evergreen central African forests and often occur in such abundance as to form a distinguishable forest sub-type with a very characteristic appearance. However, the mechanisms by which Marantaceae forests form and persist are unknown. This study was designed to elucidate the origins and mechanisms of maintenance of one type of Marantaceae forest made up of the giant herb Megaphrynium macrostachyum in the Central African Republic. M. macrostachyum often reaches high densities after logging, shifting cultivation, or fire, but there is no evidence that its abundance in the closed forest of the Ndakan study area is attributable to recent disturbance.At the landscape-scale, M. macrostachyum distribution was closely associated with canopy openness and the abundance of subsoil charcoal. Charcoal was found at 47% of sites and, in addition, five sites were found to have pottery fragments dating back approximately 600 and 2200 years BP. These results strongly suggest that M.macrostachyum patches are a persistent form of secondary forest resulting from prehistoric anthropogenic disturbance.M. macrostachyum patches were found to inhibit the establishment and growth of tree seedlings in gaps significantly, both by considerably reducing the amount of light reaching the forest floor and through underground root and rhizome competition. It is a highly light-dependent species that exhibits seed dormancy in understorey light conditions for up to 7 months and germinates most successfully in large clearings. M. macrostachyum seeds are unlikely to germinate under their own herb canopy. Vegetative growth through rhizome expansion is therefore likely to be important for the maintenance of patches. Invasion of intact forest through the colonisation of small gaps is unlikely. This study on the ecology of M. macrostachyum suggests that it is currently suffering a gradual reduction in abundance as the fores
Keywords: African Research